The Impact of Entrepreneurial Orientation and Product Innovation on Business Performance: The Role of Digitalization as an Intervening Variable - Maolani, Rivaldy; Setiawan, Rahyuniati; Herlianti, Anggun Oktavia (Manunggal Halim Jaya, 2026)
This study investigates the indirect effect of Entrepreneurial Orientation and Product Innovation on Business Performance through Digitalization as an intervening variable in the cracker industry of Garut City. As SME play a vital role in economic resilience and local development, enhancing their business performance is crucial. Entrepreneurial Orientation and Product Innovation are widely recognized as key strategic capabilities, while Digitalization offers transformative potential for operational efficiency and market expansion. A quantitative method was used with a sample of 316 cracker SME actors selected via simple random sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling with SmartPLS 3.0 version. The findings confirm that Entrepreneurial Orientation and Product Innovation significantly directly affect Business Performance and significantly influence Digitalization. Moreover, Digitalization has a strong positive effect on Business Performance and significantly mediates the relationship between Entrepreneurial Orientation and Product Innovation toward Business Performance. These findings highlight the strategic integration of entrepreneurial behavior, innovation, and digital adoption as a pathway to enhanced performance among SME in the digital era. This research contributes to theoretical development and practical guidance for small business transformation. Future studies should include broader industry samples and explore additional moderating or mediating factors such as organizational culture or customer experience.